CLINICAL DEVELOPMENT STRATEGY FOR COPIES OF PREVIOUSLY REGISTERED DRUGS. PART 3. PROTOCOL OF CLINICAL TRIAL OF BIOEQUIVALENCE - K. A. Yatsenko; E. A. Kuznetsov; A. V. Arkadjeva; V. S. Berezina (Разработка и регистрация лекарственных средств)
Recommendations presented in the article are based on current regulations and guidelines of regulatory authorities on clinical trials of bioequivalence and professional experience of authors and will be useful for medical writers to plan clinical trial lege artis. Article gives information about choice of inclusion / exclusion criteria, reference, dosages evaluated, study design, bioanalytical method validation, outcome measures and acceptance criteria for resulting protocol.